Physiotherapeutic intervention in peripheral arterial disease by functional hyperemia in diabetic patients - Cristiane Wichnieski; Flávia Natacha Salvatori Kirchhof; Pedro Cezar Beraldo; Luiz Bertassoni Neto; Christian Campos Jara
Abstract Introduction : Diabetes Mellitus (DM) is conceptualized as a public health problem with varying degrees of morbidity. The physical and functional alternatives for the treatment of circulatory complications of diabetes, such as intermittent claudication, are poorly explored. This indicates the need to search for ancillary techniques that can be used in the physical therapy treatment of diabetic patients. Objective : To investigate the effects of functional hyperemia on peripheral arterial disease in patients with diabetes. Materials and methods: This study was conducted with a group of five volunteers from the Diabetics Association of Parana (Associação Paranaense do Diabético , APAD ), who suffered from peripheral vascular disorders in the lower limbs. All subjects attended 10 sessions (twice weekly). Functional hyperemia was induced by programmed exercise therapy that consisted of walking on a treadmill. Results : There was a significant increase in mean activity time (F9,36 = 13.710; p < 0.001 ), mean walking distance (F9,36 = 27.689 ; p < 001), and mean speed (F9,36 = 15.638 ; p < .001). No statistically significant differences in the ankle-brachial index were noted. Conclusion : There was a significant increase in walking distance, time, and speed for diabetic subjects. Our findings indicate the importance of physical therapists in the supervised treatment of peripheral vascular disorders in diabetic patients.